Mitochondrial fission regulator 2 promotes cell proliferation, migration and invasion in hepatocellular carcinoma through regulating PI3K/AKT signaling pathway - Qiang Sun; Kaikun Liu; Fangjie Zheng; Xinwei Chen (Cell Division, 2025)
Abstract Objective Mitochondrial fission regulator 2 (MTFR2) is upregulated in multiple cancers, including hepatocellular carcinoma (HCC); however, its mechanistic role in HCC progression remains poorly understood. Methods MTFR2 expression in HCC tissues was analyzed using TCGA and GEO databases. Validation of MTFR2 expression levels in clinical samples and HCC cell lines was performed through qRT-PCR and western blot. Functional effects of MTFR2 overexpression and knockdown on HCC cell proliferation, migration, and invasion were assessed via CCK-8, colony formation, wound healing, and transwell assays. In vivo tumor growth was evaluated in xenograft mouse models. Results MTFR2 was significantly overexpressed in HCC tissues and cell lines. Enhanced proliferation, migration, invasion, and colony formation were observed in MTFR2-overexpressing HCC cells, whereas knockdown of MTFR2 suppressed these malignant phenotypes. Mechanistic studies demonstrated that MTFR2 promotes proliferation, migration, and invasion of HCC cells via the PI3K/AKT signaling pathway. Additionally, MTFR2 knockdown significantly attenuated tumor growth in xenograft models. Conclusion These findings demonstrate that MTFR2 promotes HCC progression via modulation of the PI3K/AKT pathway, underscoring its potential as a therapeutic target for HCC.